Noma—knowledge and practice competence among primary healthcare workers: a cross-sectional study in Burkina Faso. Issue 4 (18th December 2018) - Brattström-Stolt, Louise; Funk, Tjede; Sié, Ali; Ndiaye, Charlotte; Alfvén, Tobias
Abstract: Background: Noma is a quickly progressing, neglected opportunistic infection. It starts in the mouth as an oral lesion but can relatively quickly develop into extensive facial destruction and lead to death if not treated in time. This study aims to shed light on primary healthcare workers' practice competences in working with and knowledge of noma. Methods: A structured questionnaire using questions and case scenarios was filled out by 76 healthcare workers in Burkina Faso. Half of the nurses included in this study participated in a 2-day noma training. Data were analysed descriptively and Fisher's exact test was used to study differences between occupational groups using Stata. Results: Most healthcare workers reported having examined the mouth of children with diseases predisposing to noma. The total practice competence was poor, with almost 70% having suboptimal or very low competences. However, competences varied between different stages of noma disease. Knowledge scores varied between occupational groups. The majority of nurses and odontostomatology specialist nurses had optimal or good knowledge of noma. Significant differences in knowledge and practice competence were found between nurses who attended a 2-day training course on noma and those who did not. Conclusions: Health care workers in this study had quite poor practice competences in managing noma. The knowledge scores of these health workers were moderate. It is important for healthcare workers to be able to identify noma patients at an early stage, as at this point the disease can still be completely reversed.